Analisis Perputaran Piutang Pada PT Makmur Selaras - Evi Amelia Damayanti; Aslamiyah, Suaibatul (Indonesian Journal of Islamic Economics and Business, 2022)
An increasing number of fierce commercial enterprise competition encourages companies to achieve marketplace position, as a result businesses need a sales strategy by means of credit score which will boom the range of income. The purpose of conducting this research is due to the discovery of empirical evidence regarding the analysis of accounts receivable turnover by PT Makmur Selaras, empirical evidence obtained in the company, namely the results of company receivables that go up and down. Credit sales within the company caused some customers to experience delays in paying debts, so it is necessary to analyze how much the turnover rate of receivables from sales made by PT Makmur Selaras in the 2018-2021 period. The method used on this studies is qualitative and utilizes descriptive techniques. This studies facts uses secondary records inside the shape of money owed receivable reviews at PT Makmur Selaras. Based totally at the effects of the study, it shows that from year to year the level of receivables turnover at PT Makmur Selaras is very small, as a end result the billing finished with the aid of management is called unsuccessful, the effects of the research display that the arrears ratio fluctuates, specifically 81.21% in 2020 and sixty nine.18 % in 2021. Likewise, the billing ratio that occurs fluctuates, this means that the organisation isn't very able to amassing receivables. Unsuccessful debts receivable turnover resulting from series of unpaid receivables causes the company to enjoy a lower in revenue.